2013
DOI: 10.1080/09602011.2013.825632
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of cognitive prosthetic technology for people with memory impairments: A systematic review and meta-analysis

Abstract: Technology can compensate for memory impairment. The efficacy of assistive technology for people with memory difficulties and the methodology of selected studies are assessed. A systematic search was performed and all studies that investigated the impact of technology on memory performance for adults with impaired memory resulting from acquired brain injury (ABI) or a degenerative disease were included. Two 10-point scales were used to compare each study to an ideally reported single case experimental design (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 50 publications
5
65
3
2
Order By: Relevance
“…This review also complements the findings of the Thomas et al (2006) Cochrane review on psychological interventions for MS, showing that interventions designed to help people with cognitive impairments were inconclusive. Although this review does not support the conclusions of recent reviews of neuropsychological rehabilitation (Cicerone et al, 2011;de Joode et al, 2010) in their recommendations of the use of compensatory aids for people experiencing memory problems, it does support a recent review (Jamieson et al, 2014) that concluded there is still a specific need for investigations of technology for people with degenerative diseases.…”
Section: Agreement and Disagreement With Other Studies Or Reviewscontrasting
confidence: 48%
See 2 more Smart Citations
“…This review also complements the findings of the Thomas et al (2006) Cochrane review on psychological interventions for MS, showing that interventions designed to help people with cognitive impairments were inconclusive. Although this review does not support the conclusions of recent reviews of neuropsychological rehabilitation (Cicerone et al, 2011;de Joode et al, 2010) in their recommendations of the use of compensatory aids for people experiencing memory problems, it does support a recent review (Jamieson et al, 2014) that concluded there is still a specific need for investigations of technology for people with degenerative diseases.…”
Section: Agreement and Disagreement With Other Studies Or Reviewscontrasting
confidence: 48%
“…Cicerone et al (2011) recommended the use of external compensatory devices for people with memory problems following traumatic brain injury (TBI) or stroke; while another review (de Joode, van Heugten, Verhey, & van Boxtel, 2010) found assistive technology, such as personal digital assistants (PDA), reduced prospective memory problems after acquired brain injury (ABI). A recent meta-analysis (Jamieson, Cullen, McGee-Lennon, Brewster, & Evans, 2014) including seven group studies concluded that there was strong evidence for the efficacy of prospective memory-prompting devices for people with ABI or degenerative diseases. However, Jamieson et al (2014) only reviewed one study that included people with MS and concluded that there was a specific need for the investigation of technology for people with degenerative diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the MPD and the SLC, the d-statistic is expressed in standard deviations, whereas multilevel models can be applied meta-analytically to both raw data and standardised data (Van den Noortgate & Onghena, 2008). Non-overlap measures are also expressed in the same metric across studies, allowing their use in meta-analyses when the same indicator is applied to all data sets (e.g., Ganz et al, 2012;Jamieson, Cullen, McGee-Lennon, Brewster, & Evans, 2014).…”
Section: Dealing With Different Operative Definitionsmentioning
confidence: 99%
“…The context of application is a set of studies included in a meta-analysis on the effect of cognitive prosthetic technology (e.g., mobile phone, computer or television-based prompting device) for people with memory impairments, mostly result of acquired brain injury or degenerative disease (Jamieson et al, 2014).…”
Section: A Field Test Aimsmentioning
confidence: 99%